Association of premenstrual syndrome with BMI and dietary pattern among young adults - K. N., Ganavi; M., Ragavi (International Journal Of Community Medicine And Public Health, 2025)
Background: Premenstrual syndrome (PMS) is a group of symptoms faced by 43% of Indian Women, these symptoms simultaneously affect their daily activity and interfere with their quality of life (Majeed et al. 2022a)[1]. Objective: This study aims to find an association between nutritional status, dietary intake and pre menstrual syndrome among young adults. Materials and methods: A cross-sectional study were conducted among young adult women of age 18–26 years. 115 young adults were screened for premenstrual syndrome. Demographic data, anthropometric measures, food patterns, and lifestyle information were collected using a semi-structured questionnaire. The premenstrual syndrome score was evaluated using Padmavathi et al(Dr. Raja Sankar n.d.)[9]. premenstrual syndrome measurement tool. Nutrition counselling was provided for the participants with PMS. The relation between BMI and PMS was established using Regression analysis. Paired T test was used to check the effectiveness of the nutrition counselling by assessing the difference in PMS score. Results: The mean age group of the participants in the study were 22.9. Out of 115 participants 40% of participants had PMS. Out of 40%, 43% of the participants experience severe symptoms and 57% of the participants experience mild symptoms. The mean BMI of the participants with PMS was 22.4kg/m2. The mean percent nutrient adequacy of the participants with PMS was 90.13%. The regression model indicated there was significant relation between BMI and PMS score with P value < 0.05. There was a significant difference in PMS score before and after the nutritional counselling denoting the effectiveness of nutritional counselling in improving the premenstrual syndrome (P < 0.005). Conclusion: This study shows that BMI plays a major role in PMS Symptoms. A proper nutrition counselling can be effective in reducing the PMS Symptoms.